The Influence of the Hospital Environment on the Psychological State of Patients in the Hospital Prof. Yamin Pariaman - Agusrianto; Nirva Rantesigi (CV. Get Press Indonesia, 2026)
The hospital environment is an important factor influencing patients’ psychological conditions during treatment. Previous studies have focused more on medical and clinical services, while the impact of the hospital’s physical and social environment on patient psychology is still limited, especially in regional hospitals. This study aimed to analyze the influence of the hospital environment on patients’ psychological conditions at Prof. M. Yamin Hospital. This quantitative study used a cross-sectional design with 75 respondents selected through purposive sampling. Data were collected using valid and reliable structured questionnaires. Univariate analysis showed that 56% of respondents assessed the hospital environment as good, while 52% of patients had good psychological conditions. Bivariate analysis using the chi-square test indicated a significant relationship between the hospital environment and patients’ psychological conditions (p = 0.003). The study concludes that the hospital environment significantly affects patients’ psychological well-being. Improving environmental comfort, cleanliness, and communication quality of health workers is important to support patients’ psychological recovery and healing process.